Mycobacterium senegalense catheter-related bloodstream infection - Amin Nordin, Syafinaz; Badarol Hisham, Noralwani; Masri, Siti Norbaya; Madon, Mazriza (BMJ Publishing Group, 2024)
Catheter-related bloodstream infection (CRBSI) is one of the common healthcare-acquired infections imposing a high burden of morbidity and mortality on the patients. Non-tuberculous mycobacterium is a rare aetiology for CRBSI and poses challenges in laboratory diagnosis and clinical management. This is a case of a woman in her early 60s with underlying end-stage renal failure, diabetes mellitus and hypertension presented with a 2-week history of high-grade fever postregular haemodialysis, vomiting, lethargy and altered mental status. Blood cultures from a permanent catheter and peripheral taken concurrently yielded Mycobacterium senegalense, identified by matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry, which established the diagnosis of CRBSI atypically presented with concurrent acute intracranial bleeding and cerebrovascular infarction at initial presentation. She was started on a combination of oral azithromycin, oral amikacin and intravenous imipenem, and the permanent catheter was removed. Despite the treatments instituted, she developed septicaemia, acute myocardial infarction and macrophage activation-like syndrome, causing the patient’s death.